Biomimetic membrane nanotechnology in cerebral ischemic stroke:a promising technology for therapeutic treatment and diagnosis - Long, Yu; Zou, Zhiyan; Wu, Yuanyuan; Feng, Huiyi; Chen, Ting; Yang, Zhi; Jian, Xuemin; Yin, Yuan; Li, Xiaoan (Frontiers in Bioengineering and Biotechnology, 2025)
Cerebral ischemic stroke (CIS) is a severe cerebrovascular disease that poses numerous challenges in diagnosis and treatment, primarily attributed to blood-brain barrier (BBB) constraints and inherent drug targeting limitations. Biomimetic membrane nanotechnology, as an emerging therapeutic approach, offers a novel therapeutic strategy by emulating biological membrane structures and functions. This review comprehensively examines biomimetic nanomedicines (BMNPs) in CIS management, encompassing preparation methodologies, material characterization, and specific diagnostic/therapeutic applications. We discussed in detail various types of biomimetic nano-materials such as conventional extracellular membranes, bacterial outer membranes, and virus-like particles, and explore their capacity in enhancing BBB penetration, improving target specificity, and evading immune clearance. Current challenges regarding biosafety profiles, manufacturing quality control, targeted modification precision, and controlled drug release kinetics are delineated in this review. Looking to the future, advancing synergies between nanotechnology and biomedicine hold significant promise for optimizing CIS theranostics and expanding clinical treatment modalities.